A Cell-Free Approach Based on Phospholipid Characterization for Determination of the Cell Specific Unbound Drug Fraction (fu,cell) - Andrea Treyer; Sandra Walday; Hinnerk Boriss; Pär Matsson; Per Artursson (Pharmaceutical Research, 2019)
Purpose The intracellular fraction of unbound compound (f u,cell ) is an important parameter for accurate prediction of drug binding to intracellular targets. f u,cell is the result of a passive distribution process of drug molecules partitioning into cellular structures. Initial observations in our laboratory showed an up to 10-fold difference in the f u,cell of a given drug for different cell types. We hypothesized that these differences could be explained by the phospholipid (PL) composition of the cells, since the PL cell membrane is the major sink of unspecific drug binding. Therefore, we determined the f u,cell of 19 drugs in cell types of different origin. Method The cells were characterized for their total PL content and we used mass spectrometric PL profiling to delineate the impact of each of the four major cellular PL subspecies: phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylserine (PS) and phosphatidylinositol (PI). The cell-based experiments were compared to cell-free experiments that used beads covered by PL bilayers consisting of the most abundant PL subspecies. Results PC was found to give the largest contribution to the drug binding. Improved correlations between the cell-based and cell-free assays were obtained when affinities to all four major PL subspecies were considered. Together, our data indicate that f u,cell is influenced by PL composition of cells. Conclusion We conclude that cellular PL composition varies between cell types and that cell-specific mixtures of PLs can replace cellular assays for determination of f u,cell as a rapid, small-scale assay covering a broad dynamic range.

Effect of pyridostigmine pretreatment, HI-6 and toxogonin (®) treatment on rat tracheal smooth muscle response to cholinergic stimulation after organophosphorus inhalation exposure - Per Walday; Pal Aas; Trond Haider; Frode Fonnum (Archives of Toxicology, 1993)